Association between ambient ozone exposure during pregnancy and risk of preterm birth in Guangdong Province - Peng HU; Shanshan RAN; Qingmei LIN; Yin YANG; Zilong ZHANG; Xiaoling GUO; Yonggui GAO; Jinde ZHAO; Hualiang LIN (环境与职业医学)
BackgroundAir pollution exposure has a significant impact on maternal and child health. However, the research on the association between ambient ozone (O3) exposure during pregnancy and the risk of premature birth in newborns is limited, and the conclusions are inconsistent. ObjectiveTo investigate the association of ambient O3 exposure during pregnancy with the risk of preterm birth in Guangdong Province. MethodsData of pregnant women in Guangzhou from 2013 to 2019 and Foshan from 2018 to 2023 were collected, and O3 concentrations during different trimesters were assessed according to maternal residential addresses. Bilinear interpolation was used to evaluate the concentrations of air pollution. A cohort study design was adopted in our study. Restricted cubic spline curves were used to evaluate the exposure-response relationship between O3 exposure and preterm birth risk and explore potential exposure threshold of O3. Logistic regression models were used to evaluate the association of O3 exposure with preterm birth. ResultsA total of 702 924 pregnant women were included in this study, of whom 43 051 (6.12%) were preterm. The average O3 exposure concentrations of pregnant women during the first, second, third, and whole trimesters were 95.51, 97.51, 100.60, and 97.87 μg·m−3, respectively. We observed J-shaped associations between O3 exposure and preterm birth risk during the second, third, and whole trimesters of pregnancy using restricted cubic spline curves. This study found that there were threshold concentrations between O3 exposure and preterm birth risk during different gestational periods, and the threshold concentrations in the first, second, third, and whole trimesters were 112.32, 99.83, 111.74, and 112.46 μg·m−3, respectively. During the second, third, and whole trimesters of pregnancy, after adjusting for maternal age, baby sex, pre-pregnancy body mass index, mode of delivery, baby birth weight, gestational diabetes, and gestational hypertension, the odds ratios (OR) of preterm birth were 1.02 (95%CI: 1.01, 1.04), 1.02 (95%CI: 1.00, 1.03), and 1.17 (95%CI: 1.13, 1.21) for each 10 μg·m−3 increase in O3 concentration above the O3 threshold. No significant association was found between O3 exposure and the risk of preterm birth during the first trimester. ConclusionThere is a nonlinear association between the risk of preterm birth and O3 exposure during pregnancy, and higher concentrations of O3 exposure during pregnancy are associated with the risk of preterm birth. Above the O3 threshold concentration during pregnancy, especially during the second, third, and whole trimesters, the risk of preterm birth elevates with the increase of O3 exposure concentrations.